Implementasi Metode Weighted Product Dalam Sistem Pendukung Keputusan Pemilihan Layanan Uang Elektronik Terbaik - Wasti, Melati; Hartini, Sari; Rinawati, Rinawati (Jurnal teknika, 2019)
This research was conducted to assist users in choosing the best electronic money. Where electronic money is easier to use than conventional money. By using five criteria, namely: convenience, security, promotion, speed, and convenience. This research was conducted on electronic money users in the city of Bekasi with a population of 3,013,851 people using a sample of 44 respondents. The method used is the weighted product method. The results of this study indicate that the first alternative electronic money recommendation obtained by OVO has a value of 0.391 with very positive criteria, namely convenience value (K1) = 206, security (K2) = 204, promotion (K3) = 169, speed (K4 ) = 203, convenience (K5) = 183. The second alternative electronic money recommendation obtained by Go-Pay has a value of 0.359 with criteria that have a very positive effect, namely convenience value (K1) = 182, security (K2) = 168, promotion (K3 ) = 166, speed (K4) = 183, comfort (K5) = 180. The third alternative recommendation for electronic money obtained by Dana has a value of 0.227 with criteria that have a very positive effect, namely convenience value (K1) = 115, security (K2) = 126, promotion (K3) = 117 speed (K4) = 124, comfort (K5) = 111.